The Rise of Neoliberal Rhetoric and the Intersection of Modern Day Medicaid Priority: A Population Study of Young People in Nursing Homes - Kawam, Elisa (Disability Studies Quarterly, 2012)
This exploratory study aims to examine the present state of young people (<65 years of age) who reside in nursing homes due to traumatic and permanent injury. Due to the gap in the literature, this population is underrepresented in professional development training as well as service provision. This lack of appropriate and affordable care has severe consequences for nursing home residents on all domains: biological, psychological, social and spiritual. This population is expected to grow dramatically over the coming years and there is little to no advocacy for those residents. Furthermore, this paper discusses the effect of neoliberalism economic ideology in the United States and its effect on Medicaid spending priority, service allocation and overall quality of life for young people in nursing homes. Every level of society must act to reform healthcare priorities and advocate for this hidden and very vulnerable population. Keywords: Nursing homes, young people, Medicaid